Performing power in Nigeria : identity, politics, and Pentecostalism - Adelakun, Abimbola Adunni (African identities : past and present., 2023)
A fresh and interdisciplinary study of faith and social culture in Nigeria, Abimbola A. Adelakun uses extensive archival material, interviews and fieldwork to explore how Nigerian Pentecostals use performance to mark their self-distinction as a people of power.